Santri MBKM (Merdeka Belajar-Kampus Merdeka) Program in Development Self-Student - Kholilur Rahman; Lilis Setiawati; Fathor Rozi (Al-Ta'lim, 2023)
MBKM Santri is a Merdeka belajar – Kampus Merdeka program by Santri to carry out community service at target Islamic boarding schools and partner Islamic boarding schools directly. Student independent campus activities are expected to be able to hone the soft skills of partnership, work together in cross-disciplinary teams, and lead students at the destination Islamic Boarding School and other Partner Islamic Boarding Schools. This study used a qualitative approach, carried out at the Nurul Jadid Paiton Islamic Boarding School with 10 MBKM participating students as subjects. This type of research uses case studies. The results of this study indicate that MBKM Santri is implemented through; developing student potential, establishing student interpersonal relationships, developing student skills, and fostering new motivation for students. Students can further develop their abilities by participating in activities held by partner campuses and Islamic boarding schools. The existence of the student MBKM is intended so that students can further develop their abilities by participating in activities held by the destination campus and pesantren/partners. MBKM Santri students plan to implement several activities carried out on the destination campus to their partner campus / campus itself.